Studying the physiological and biochemical properties of lactic bacteria cultures in the creation of sourdough for bread - Isabekova, M.S.; Umiraliyeva, L.B. (Fundamental and Experimental Biology, 2022)
The article presents the results of screening lactic acid bacteria cultures of the genus Lactobacillus and Pedio-coccus from the collection of Kazakh Scientific Research Institute of Processing and Food Industry, previous-ly isolated from wheat grain, flour, rye starter cultures, as well as kumis and shubat. For a comprehensive as-sessment of probiotic properties of the selected 7 strains of lactic acid bacteria, their physiological and bio-chemical properties were studied: acid-forming, antagonistic activity, saccharolytic profile, resistance to vari-ous concentrations of bile, sodium chloride, growth at different pH values, antibiotic resistance. As a result of strains screening 5 most active cultures of lactic acid bacteria were selected for inclusion in the sourdough for bread: Limosilactobacillus pontis 9K3, Limosilactobacillus fermentum 3Ш1, Lb. paracasei 82, Lb. paracasei 114, Lacticaseibacillus paracasei 126.The selection criteria were high enzymatic, acid-forming, proteolytic and antagonistic activity of the strains against opportunistic and pathogenic microflora (B. subtilis ATCC 6633, Escherichia coli-1257, Staphylococcus sp.209-P, Salmonella Typhimurium). We show that this result of the analysis indicates the prospects of using a consortium of these cultures to obtain a probiotic starter culture for bakery products. This, in turn, will increase production efficiency, ensure the quality and safety of food products in the baking industry.